Update Breast Cancer 2022 Part 2 - Advanced Stage Breast Cancer - Müller, Volkmar; Welslau, Manfred; Lüftner, Diana; Schütz, Florian; Stickeler, Elmar; Fasching, Peter; Janni, Wolfgang; Thomssen, Christoph; Witzel, Isabell; Fehm, Tanja N.; Belleville, Erik; Bader, Simon; et al. (Geburtshilfe und Frauenheilkunde, 2022)
For patients with advanced breast cancer, several novel therapies have emerged in recent years, including CDK4/6 inhibitors, immune checkpoint inhibitors, PARP inhibitors, alpelisib, tucatinib and trastuzumab-deruxtecan, and sacituzumab-govitecan, which have transformed and expanded the therapeutic landscape for patients with advanced breast cancer. Some of these substances have now been approved for use in the early stages of the disease, or are expected to be approved in the near future, so the therapeutic landscape will change once again. Therefore, current scientific efforts are focused on the introduction of new substances and understanding their mechanisms of progression and efficacy. This review summarizes recent developments with reference to recent publications and conferences. Findings on the treatment of patients with HER2-positive breast cancer and brain metastases are presented, as are a number of studies looking at biomarkers in patients with HER2-negative, hormone receptor-positive breast cancer. In particular, the introduction of oral selective estrogen receptor degraders provides new opportunities to establish biomarker-based therapy. Molecular diagnostics is establishing itself as a diagnostic marker and parameter of progression.
CRIS-Team Scopus Importer:2022-08-05
Keywords: ADC; biomarker; breast cancer; metastatic; PD-L1